Modeling pool sediment dynamics in a mountain river - Rathburn, Sara L., author (Colorado State University. Libraries, 2001)
An increasingly important source of sediment into river systems is sediment that accumulates within reservoirs and is subsequently released into the downstream ecosystem. In Colorado alone, five large-scale sediment releases from reservoirs within the last decade have resulted in a host of environmental hazards, particularly the loss of aquatic biota and their habitat. The most recent example occurred in September 1996 when approximately 7,000 m3 of clay- to gravel-sized sediment were released from Halligan Dam into the North Fork Cache la Poudre River in northern Colorado. The sediment caused extensive aggradation of the original cobble-boulder bed, primarily in pools, and complete fish mortality for 12 km downstream from the dam. Because of the thriving, pre-release wild trout fishery downstream from Halligan Reservoir, flushing of sediment from pools to recreate overwinter fish habitat was of prime concern. The purpose of this investigation was to evaluate the applicability of various hydraulic and sediment transport models as predictors of pool recovery along the steep gradient, bedrock-controlled North Fork River. Two modeling scenarios representing a low and high flushing discharge were modeled using one- and semi-two dimensional sediment transport models, HEC-6 and GSTARS2.0, respectively. The models were calibrated against quantitative measurements of pool bed elevation obtained during field surveys. HEC-6 results indicate that long-term, robust simulations yield the closest agreement between predicted and measured pool bed elevation change. Greater than 50 percent of the actual scour and deposition within three pools was modeled using HEC-6.Modeling accuracy using GSTARS2.0 was considerably more variable, and no pool-wide trends were obtained. A two-dimensional, finite element hydraulic model, RMA2, improved delineation of flow hydraulics in areas of flow separation and recirculation within a compound pool.RMA2 results of depth-averaged velocity magnitude and vectors broadly agree with timed photographs of surface flow patterns, and correspond with velocity measurements for low-velocity areas such as eddy pools. Patterns of boundary shear stress and a particle stability index accurately predict gross areas of scour and deposition, but fail to represent the simultaneous aggradation and degradation measured in pools. Estimates of bedload transport capacity from the two-dimensional modeling results are one order of magnitude greater than measured transport rates, and indicate that supply-limited conditions existed along the North Fork following a clear-water flushing release. Further correlations between observed and modeled sedimentation patterns are hindered by the disparity in resolution between the field data and modeled results; field-based cross sectional information is quickly outstripped by the finite element model RMA2. Finally, a conceptual model of pool sediment dynamics was developed for water resource specialists as an alternative to the time-intensive effort and expertise required of the numerical modeling. Predictable sites of channel aggradation and degradation resulting from a sediment pulse are identified on a reach-scale hierarchy. Processes of sediment delivery, storage, and transfer into and out of eddies that influence fish occur on the width scale, however. Sedimentation within laterally confined pools is dependent on pool geometry, distance downstream from the dam (a surrogate of sediment supply), and the duration and magnitude of flows following the release. At low flows, sediment deposition is restricted to small areas of recirculating flow. As discharge increases, migration of the separation point and development of a strong shear zone limits the transfer of sediment between the eddy and the main flow. The sediment release from Halligan induced persistent, long-term storage of fine sediment because of an elevated channel bed and loss of channel capacity. Recognition of the hazards associated with a large influx of sediment into a riverine ecosystem is critical for a greater understanding of the effects of sediment releases, and future management of sediment within reservoirs.
Keywords: Sediment transport -- Colorado -- Cache la Poudre River